3t-2/4 - 2t+3/3 = 2/3 - t
Attachments:
![](https://hi-static.z-dn.net/files/d46/d1b4c8408bc956a0544bb3eabdc5d843.jpg)
Answers
Answered by
0
t = 6.5
Step-by-step explanation:
3t-2/4 -2t +3/3 = 2/3-t
9t-6-8t+12/12 = 2-3t/3
t+6/12 = 2-3t/3
3(t+6) = (2-3t)12
3t+18 = 24-36t
3t+36t = 24-18
39t = 6
t = 39/6
t = 6.5
Answered by
1
t = 2
solution in image.
cheese
:)
Attachments:
![](https://hi-static.z-dn.net/files/de8/d43e98cbca91987a3f2ec1c25754becf.jpg)
![](https://hi-static.z-dn.net/files/d83/b1782a21750203e67d4edf76468ef203.jpg)
Similar questions
English,
1 month ago
Social Sciences,
1 month ago
Business Studies,
3 months ago
English,
3 months ago
English,
11 months ago
Math,
11 months ago